2004
DOI: 10.1136/thx.2003.019588
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic obstructive pulmonary disease and systemic inflammation: a systematic review and a meta-analysis

Abstract: Background: Individuals with chronic obstructive pulmonary disease (COPD) are at increased risk of cardiovascular diseases, osteoporosis, and muscle wasting. Systemic inflammation may be involved in the pathogenesis of these disorders. A study was undertaken to determine whether systemic inflammation is present in stable COPD. Methods: A systematic review was conducted of studies which reported on the relationship between COPD, forced expiratory volume in 1 second (FEV 1 ) or forced vital capacity (FVC), and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
1,139
8
118

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,564 publications
(1,343 citation statements)
references
References 47 publications
58
1,139
8
118
Order By: Relevance
“…IL-1β and TNFα [2,3]. As demonstrated in Figure 3B, stimulation of HPAEC with IL-1β and TNFα increased the levels of miR-223 at all time points assessed.…”
Section: Inflammatory Cytokines Induce the Levels Of Mir-223mentioning
confidence: 70%
See 2 more Smart Citations
“…IL-1β and TNFα [2,3]. As demonstrated in Figure 3B, stimulation of HPAEC with IL-1β and TNFα increased the levels of miR-223 at all time points assessed.…”
Section: Inflammatory Cytokines Induce the Levels Of Mir-223mentioning
confidence: 70%
“…In stimulation experiments using endothelial cells that, in vivo, reflect the first responders of the lungs to these proinflammatory signals, we found that IL-1β and TNFα significantly induced the levels of miR-223 in a time-dependent manner. These cytokines have been described as key inflammatory mediators in COPD [2,3] and their activity in COPD patients might explain the significant upregulation of miR-223 levels in vivo as shown by Ezzie and colleagues [21]. Both cytokines are activators of the transcription factor nuclear factor kappa B (NF-κB).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mechanism of COPD in RA has been suggested by prior studies to be autoimmune or inflammatory, with cytokines and chemokines contributing to lung tissue destruction [1,8,9]. Studies looking at association of reduced lung function tests with systemic inflammatory markers have shown that COPD patients have higher levels of circulating inflammatory markers including leukocytes, fibrinogen, ESR, CRP, tumor necrosis factor-α, suggesting that systemic inflammation may have a role in COPD [11]. Also, increased production of autoantibodies against a broad spectrum of self-antigens has been demonstrated in COPD, suggesting the role of autoimmunity [12].…”
Section: Discussionmentioning
confidence: 99%
“…In COPD, lung hyperinflation seems to be one factor of interest as it results in a mechanical disadvantage, although the contribution of increased work of breathing to cachexia is not clear (Engelen et al, 1999;Mannix et al, 1999;Budweiser et al, 2005Budweiser et al, , 2006b). Conversely, evidence has been accumulated that suggests a relationship to elevated levels of inflammatory cytokines and the systemic manifestation of the disease (Gan et al, 2004;Broekhuizen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%